Implementation of Lean UX to Improve the Quality of User Experience (Case Study: PT. XYZ) - Yusuf, Muhamad; Nasrulloh, Anas; Ikhwanudin, Aolia; Toifur, Tubagus; Ramadhan, Aditya Duta; Mas’ud, Ibnu (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
The importance of websites in the modern digital world encourages various companies to develop effective user interfaces (UI) and user experiences (UX). This study aims to design the UI/UX design of PT. XYZ's website using the Lean UX method, which focuses on active collaboration with users in developing a Minimum Viable Product (MVP). The Lean UX method involves four main stages: Declare Assumptions, Create MVP, Run Experiments, and Feedback and Research. Testing was carried out using the System Usability Scale (SUS) to measure the level of usability. The results of the study showed that the new UI/UX design significantly improved efficiency and user satisfaction, with a SUS value of 80, which is included in the "Excellent" category. This study makes a significant contribution to website development in the digital sector, especially in designing user-friendly interfaces that are centered on user needs.